Lingue d’invenzione nella letteratura per l’infanzia: Swift, Carroll, Rodari - Lepri, Chiara (Studi sulla Formazione/Open Journal of Education, 2009)
The chidhood literature is a complex area of educational studies. Its linguage is near to artistic disciplines and it is an intresting aspect to reflect. This essay intends to analyse creative linguage in three important Authors: Swift, Carrol and Rodari and it want to find to the recurrent elements.